Internationalization channels and firm financial performance among Asia-Pacific corporations. Does ESG integration in business matter? - Hussain, Waleed; Ong, Tze San; Teh, Boon Heng; Javeed, Sohail Ahmad (Springer Science and Business Media B.V., 2026)
Growing global cooperation between nations and organizations regarding sustainability concerns has led to increased emphasis on research into firm internationalization (INT). The purpose of this study is to examine the impact of different dimensions of firm internationalization on firm financial performance (FFP), particularly emphasizing the moderating role of environmental, social, and governance (ESG) performance of multinational corporations. Using a panel data set comprising 1708 corporations from the Asia-Pacific region from 2002 to 2023, the findings of Panel OLS, along with robust two-stage least square estimations, reveal that the firm internationalization significantly and positively affects FFP. The study also highlights how sustainability performance potentially moderates the relationship between INT and FFP. The study offers practical implications for managers, regulatory authorities, and other policymakers for sustainable development business models. By choosing the right international channel and sustainability initiative, firms can maximize the benefits of internationalization.